Secondary mastopexy with exchange of prosthesis: mirror “D” technique - Juan Carlos Sánchez López; Patrícia Erazo (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Breast implantation combined with mastopexy is challenging, not only because a standard procedure is lacking, but also because of the high potential for complications, including a high rate of post-surgical revision. Originally intended for primary mastopexy and inclusion of silicone implants in hypoplastic breasts with moderate to severe ptosis, the use of the mirror "D" technique is now extended to treatment of ptosis recurrence with displacement of prostheses, with or without capsular contracture and/or unsightly scars. Method: The procedure described was performed in 90 patients, using specific marking to determine block resection of skin and underlying parenchyma for symmetrization. The procedure included use of a medial pedicle flap and exchange of original implants for textured, high-profile, round silicone prostheses with equal volumes bilaterally and positioned in the submuscular plane, resulting in a final vertical scar. Results: No surgical revision was required in any of the cases. There was no occurrence of postoperative infection or necrosis of the nipple-areola complex or scar. The average parenchyma resection was 80 g. Eighty-nine patients (98.8%) were submitted to resection of different volumes. The average prosthesis volume was 300 mL. The length of the vertical scar was stable with an average of 6.5 cm after 2 years. The results were considered satisfactory according to patient assessment. Conclusion: Secondary mastopexy is a more complex surgery due to severe atrophy of the tissue as a result of previous surgery. Its benefits include improved symmetrization, thinner scars and reduction in tension on the nipple-areola complex, long-lasting results, and a high degree of patient satisfaction.